Sequential therapy of crizotinib followed by alectinib for non-small cell lung cancer harbouring anaplastic lymphoma kinase rearrangement (WJOG9516L): A multicenter retrospective cohort study. (March 2021) - Ito, Kentaro; Yamanaka, Takeharu; Hayashi, Hidetoshi; Hattori, Yoshihiro; Nishino, Kazumi; Kobayashi, Haruki; Oya, Yuko; Yokoyama, Toshihide; Seto, Takashi; Azuma, Koichi; Fukui, Tomoya; Kozuki, Toshiyuki; et al.
Abstract: Background: The data of sequential therapy of anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) in clinical practice have been limited. Methods: We reviewed the clinical data of patients with ALK-rearranged non-small cell lung cancer who received crizotinib (CRZ) or alectinib (ALEC) between May 2012 and December 2016. Patients were divided into two groups based on the first-administered ALK-TKI, the CRZ or ALEC group. The combined time-to-treatment failure (TTF) was defined as the sum of the 'TTF of CRZ' plus the 'TTF of ALEC' if patients were treated with CRZ followed by ALEC in the CRZ group. The primary end-point is the comparison between the combined TTF and the TTF of ALEC in the ALEC group. Results: Of 864 patients enrolled from 61 institutions, 840 patients were analysed. There were 535 of 305 patients in the CRZ/ALEC groups. The combined TTF in the CRZ group was significantly longer than TTF in the ALEC group (median, 34.4 versus 27.2 months; hazard ratio [HR], 0.709; P = 0.0044). However, there was no significant difference in overall survival (OS) between the patients who received ALEC after CRZ in the CRZ group and the patients in the ALEC group (median, 88.4 months versus. not reached; HR, 1.048; P = 0.7770). In the whole population, the CRZ group had a significantly shorter OS than the ALEC group (median, 53.6 months versus not reached; HR, 1.821, P < 0.0001). Conclusion: The combined TTF in the CRZ group was significantly longer than the TTF in the ALEC group; however, OS benefit of sequential therapy against ALEC as the first ALK-TKI was not shown. Highlights: Large-scale real-world data showed longer progression-free survival of alectinib than crizotinib. But, propensity score analysis of overall survival could not show the superiority of alectinib. Poor responders to crizotinib had poorer response also to alectinib. Ceritinib or lorlatinib showed activity even after crizotinib or alectinib therapy. Meanwhile, immunotherapy could not show clinical benefit in our data.